Nokia Siemens Networks: Just Doing Business – or Supporting an Oppressive Regime? - Schrempf, Judith (2011)
This case study examines the relevance of taking social and political factors into consideration when a corporation is making a key business decision. In September 2009, Simon Beresford-Wylie, the outgoing CEO of Nokia Siemens Networks (NSN), was reviewing the company’s achievements – while acknowledging the latest public criticism regarding NSN’s business relationship with the Iranian government. In the summer of 2009, NSN was accused of complicity in human rights violations linked to Iran’s presidential election. The company sold network infrastructure and software solutions to the Iranian government, which then used this technology to observe, block, and control domestic communications. Should NSN have acted differently? Students are asked to examine the economic and moral arguments for and against selling products to an oppressive regime that might then use those products to violate human rights. In such a case, does the corporation bear co-responsibility for human rights violations committed by an oppressive regime?
Keywords: Nokia Siemens Networks; Corporate Social Responsibility; Human Rights; Complicity; Censorship